Quantification of liver and kidney phosphofructokinase by radioimmunoassay in fed, starved and alloxan-diabetic rats. - Donofrio, J C (1984)
A newly developed specific radioimmunoassay was used to quantify phosphofructokinase protein directly and independently of assayable activity in liver and kidney cytosol of normal fed, starved and alloxan-diabetic rats. In the fed state, liver phosphofructokinase concentration was 0.096 microM and the kidney enzyme was 0.086 microM (mumol/kg of tissue). In the starved state (24h), liver and kidney phosphofructokinase concentrations decreased by 30%. Prolonged starvation up to 72h did not further decrease enzyme concentration. In liver, total enzyme content during starvation declined by more than 50%, secondary also to a decrease in liver weight. In the alloxan-diabetic rats, there was a 22% decrease in enzyme protein concentration in liver and kidney. Total enzyme content per liver actually decreased much more (46%), because diabetes also resulted in a decrease in liver size. In conjunction with assayable activity measurements, the results of the radioimmunoassay allowed us to calculate the apparent specific activity of the enzyme. The specific activity of the kidney enzyme was 2-3 times that of the liver. Little or no change in specific activity of the liver or kidney enzyme occurred as a result of starvation or chemically induced diabetes. Tissue enzyme concentrations of phosphofructokinase unequivocally reconcile the ultimate results of changing rates of synthesis and degradation and are useful data in the design of spectrophotometric, kinetic, aggregation-disaggregation and other studies.